2001
DOI: 10.1042/0264-6021:3600461
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of type-II collagen gene expression during human chondrocyte de-differentiation and recovery of chondrocyte-specific phenotype in culture involves Sry-type high-mobility-group box (SOX) transcription factors

Abstract: During ex vivo growth as monolayer cultures, chondrocytes proliferate and undergo a process of de-differentiation. This process involves a change in morphology and a change from expression of chondrocyte-specific genes to that of genes that are normally expressed in fibroblasts. Transfer of the monolayer chondrocyte culture to three-dimensional culture systems induces the cells to re-acquire a chondrocyte-specific phenotype and produce a cartilaginous-like tissue in vitro. We investigated mechanisms involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 51 publications
6
60
0
Order By: Relevance
“…SOX9 is a member of the sex-determining region Y-type high mobility group box protein family and has been shown to be required for chondrocyte-specific gene expression and chondrogenesis (48)(49)(50). We also observed the involvement of the SOX factors in the dedifferentiation process (51). Interestingly, recent investigations have established a connection between SOX9 and the protein CD-RAP.…”
Section: Discussionsupporting
confidence: 58%
“…SOX9 is a member of the sex-determining region Y-type high mobility group box protein family and has been shown to be required for chondrocyte-specific gene expression and chondrogenesis (48)(49)(50). We also observed the involvement of the SOX factors in the dedifferentiation process (51). Interestingly, recent investigations have established a connection between SOX9 and the protein CD-RAP.…”
Section: Discussionsupporting
confidence: 58%
“…SOX9 is a transcription factor that regulates the expression of a series of cartilage matrix genes during chondrogenesis (49). With the progression of dedifferentiation, the expression level and the transcription activity of SOX9 decline (50,51), while the activity of SOX9 may be negatively regulated by ERK signaling (47). We evaluated the expression level of SOX9 in monolayer-cultured chondrocytes and found that it did not change significantly in the early phase of dedifferentiation investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic mobility-shift assays (EMSAs) were carried out as previously described with minor modifications (25). Briefly, binding reactions consisted of 12.5 mM Hepes, pH 7.9, 50 -100 mM NaCl, 5% glycerol, 2 mg/ml bovine serum albumin, 2 g poly(dG-dC), 0.1 mM EDTA, 0.1 mM dithiothreitol, 1 ng of 32 P-end labeled double-stranded oligonucleotide probe, and 10 -15 g of nuclear protein.…”
Section: Figmentioning
confidence: 99%